Evaluation of knowledge and experience on the success of inferior alveolar nerve block technique - Ehsan Aliabadi; Esfandiar Keshavarz (Tehran University of Medical Sciences, 2020)
Background and Aims: The inferior alveolar nerve block (IANB) is the most frequently used technique for mandibular anesthesia. Due to the many factors which can cause its failure, the aim of this study was to evaluate the efficacy of experience and knowledge in the success rate of IANB technique. Materials and Methods: : In this study, 115 students of Shiraz Dental school were participated in two groups. One group contained 53 novice students and another group 62 students with one year experience in IANB injection. Each student accomplished injection once and then success or failure of the injection was examined. In order to evaluate the students' knowledge, each student was asked to fill out a questioner including 6 questions related to the instruction of the injection. Data were then collected, coded, and analyzed by SPSS18 using Chi square with a significant level of 0.05. Results: The rates of knowledge in novice and experienced group were 71.6% and 86.3%, respectively. The success rates of IANB were 47.1% in novice group and 64.3% in experienced group. The success rates of IANB and knowledge were significantly higher in the experienced group compared with the novice group. (P=0.02 and P=0.01, respectively) There was no significant difference between male and female (P=0.06). Conclusion: The results showed that knowledge and experience could play an important role in the success rate of IANB technique.